Poultry Farmers` Utilization of Information in Lagelu Local Government Area, Oyo State of Nigeria - Fawole, O. Pipy (International Journal of Poultry Science, 2006)
This study investigated poultry farmers` access and utilization of extension information in Lagelu Local Government Area of Oyo State. Data were collected using structured questionnaire. The results indicate that poultry farmers obtain information from a variety of sources with television been the most prominent (68%). Animal health it was found is the top information need of poultry farmers (52%). Severe constraints to poultry production are cost of obtaining information (64%), veterinary services (66%) and non-availability of extension agents (63%). The study further shows that poultry farmers` sex and educational level are significantly related to sources of information. Similarly, poultry farmers` sex and educational level are related to their utilization of information. Non availability of extension agents, cost of inputs are also significantly related to farmers` utilization of information. The results imply that paucity of extension workers and increased cost of inputs reduce the probability of farmers utilizing available technologies or information.